Interlanguage Analysis of the Vocational High School Students of SMK Muhammadiyah 3 Surakarta - Putri Itsna Ulayya; Endang Fauziati; Malikatul Laila (Dinasti International Journal of Education Management and Social Science, 2025)
The research entitled Interlanguage Analysis of the Vocational School Students of SMK Muhammadiyah 3 Surakarta aims to describe the interlanguage of tenth-grade students of SMK Muhammadiyah 3 Surakarta through an analysis of linguistic errors found in students’ writing. The background of this research is derived from the students’ low writing proficiency, which is influenced by their first language, limited mastery of grammatical structures, and inconsistent application of target language rules. This study employed a descriptive qualitative method with data consisting of students’ written texts collected from classroom assignments. The data were analysed to identify forms of interlanguage, the sources of their occurrence, and the relationship between these errors and the students’ language development stages. The findings show that students produce various interlanguage features, particularly in the use of verb forms, tenses, prepositions, and sentence structure. These errors are influenced by first language transfer, overgeneralization, simplification, and learning strategies. The results indicate that the students’ interlanguage is still in an unstable developmental stage and requiring continuous guidance. This study concluded that interlanguage analysis is essential for understanding students’ language development and for helping teachers design more effective instructional strategies.